Storytelling as a Peace Education in Interfaith Dialogue: An Experience Among Selected University Students - Mohd Khambali @ Hambali, Khadijah; Abdul Rahman, Nur Farhana; Senin, Nurhanisah; Haji Dollah, Sri Rahayu (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
The study is aimed at exploring storytelling approach as a medium for the transformative teaching and learning of interfaith dialogue among undergraduate students. Due to their upbringing and environment, the students do not have the oppurtunity to know other religions and culture better. This is especially true for those who lived only among their own ethnic. Therefore, this research is aimed at promoting interfaith dialogue as well as fostering peace and harmony between students of the Department of ‘Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya; Department of Theology and Philosophy, National University of Malaysia and Centre for Religion and Society of Malaysia Theological Seminary. Through group conversation, fieldwork and workshop with the students, this study demonstrates that peace education through storytelling can be utilized as a tool of narrative truth-telling, aimed at restoring inter-personal relationships, healing traumatic experiences and promoting social coexistence (ta’ayush). This approach enables to foster interfaith dialogue among the students thus, contributes to the development of a culture of peace. The storytelling approach with a member from ‘the other’ group can be interpreted as a desire to proclaim the ‘unheard’ voices and feelings to be shared with ‘the other’. It connects with the practice of active listening to overcome prejudice, leading towards the transformative learning process. Peace storytelling may therefore, be seen as an understanding ‘the others’. This study also recommends the significance on creating environments to foster inter-religious dialogue, expanding formats of interfaith dialogue and increasing religious study through education and training.